Product Innovation Strategy and Dynamic Environment Against the Improvement of Company Performance at MSME in Kulon Progo - Dari, Wulan; Isfianadewi, Dessy (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to improve company performance at MSME by implementing product innovation strategies supported by dynamic environments. This research used a quantitative approach and the structural equation model (SEM) method. Data collection employed questionnaire methods, and data analysis was tested using AMOS. This study’s population was MSMEs registered at the Cooperatives and MSME Office in Kulon Progo Regency in 2019. Besides, the respondents sampled in this study were 200 MSMEs focusing on the culinary, handicraft, and fashion industry sectors. This study’s results proved that the dynamic environment positively and significantly influenced product innovation strategies. Then, product innovation positively and significantly affected firm performance. Furthermore, the dynamic environment had a positive and significant influence on firm performance. The product innovation strategy mediated the relationship between the dynamic environment and firm performance. This study contributes to the MSMEs’ owners being aware of the importance of improving company performance by continuously implementing product innovation strategies because consumers are smarter to choose and decide where and what products to consume as their needs and desires’ fulfillment. This product innovation strategy could mediate the influence of the dynamic environment and company performance.